Styro Enterprise : Styronomo / Khabir Nabil Mohd Sa'id ... [et al.] - Mohd Sa'id, Khabir Nabil; Zainal Abidin, Zuliana Umirah; Ali, Maizatul Izzlyen; Ahmad Sabki, Wan Ainul Umairah; Abu Sahit, Mohamad Imran; Pakarudin, Muhammad wazif (2017)
As for the business, we are producing a multi-purpose product which consist of glue and shellac for Malaysian. People nowadays want something that is simple, easy to use and can act effectively but also comes at a reasonable price. Our product comes in convenient packaging form to reduce the manufacturing cost, market price and also ready and easy to use.